1999
DOI: 10.1007/s002530051463
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of indene bioconversion genes from Rhodococcus strain I24

Abstract: Rhodococcus strain 124 is able to convert indene into indandiol via the actions of at least two dioxygenase systems and a putative monooxygenase system. We have identified a cosmid clone from 124 genomic DNA that is able to confer the ability to convert indene to indandiol upon Rhodococcus erythropolis SQ1, a strain that normally can not convert or metabolize indene. HPLC analysis reveals that the transformed SQ1 strain produces cis-(1R,2S)-indandiol, suggesting that the cosmid clone encodes a naphthalenetype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
1
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 27 publications
1
56
1
1
Order By: Relevance
“…A few polypeptides, including the two subunits of Pdo2, were synthesized only in the presence of a PAH, indicating that they are subjected to a regulation mechanism different from that controlling the enzymes induced by benzoate. Finally, we observed that some polypeptides were detectable only in pyrene-induced cells and that other proteins, including a dihydrodiol dehydrogenase, were found exclusively or predomi- The two dioxygenase terminal components described herein were found to be related to enzymes found in four actinomycete species, including two Rhodococcus strains (27,38), Nocardioides strain KP7 (34), and Mycobacterium strain PYR-1 (24). In previous reports, phylogenetic analysis indicated that these dioxygenases formed a cluster of enzymes distinct from other dioxygenases (24,34).…”
Section: Discussionmentioning
confidence: 79%
“…A few polypeptides, including the two subunits of Pdo2, were synthesized only in the presence of a PAH, indicating that they are subjected to a regulation mechanism different from that controlling the enzymes induced by benzoate. Finally, we observed that some polypeptides were detectable only in pyrene-induced cells and that other proteins, including a dihydrodiol dehydrogenase, were found exclusively or predomi- The two dioxygenase terminal components described herein were found to be related to enzymes found in four actinomycete species, including two Rhodococcus strains (27,38), Nocardioides strain KP7 (34), and Mycobacterium strain PYR-1 (24). In previous reports, phylogenetic analysis indicated that these dioxygenases formed a cluster of enzymes distinct from other dioxygenases (24,34).…”
Section: Discussionmentioning
confidence: 79%
“…Sequence alignments indicated that PhtB showed considerable divergence from A. keyseri 12B PhtB (Eaton, 2001), yet was related to Terrabacter sp. DBF63 PhtB (Habe et al, 2003) and other dihydrodiol dehydrogenases (Larkin et al, 1999;Masai et al, 1995;Saito et al, 2000;Treadway et al, 1999). Phylogenetic analysis of PhtB suggests, however, that the protein is closely related to PhtB of both Terrabacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis of these oxygenase components, NidA, NidA3 and PhtAa, showed that they clustered with a new group of α subunits found in Nocardioides, Rhodococcus, Terrabacter, Arthrobacter and other Mycobacterium spp. [20][21][22][23][24][25]. Interestingly, RHO genes found in this group of bacteria appear to have features in common; genes for ETC components are not always closely positioned with oxygenase genes (genetic discreteness) and limited numbers of ferredoxin and reductase components are shared by multiple oxygenases (numerical imbalance).…”
Section: Introductionmentioning
confidence: 97%